Effects of replacing wheat bran with palm kernel cake or fermented palm kernel cake on the growth performance, intestinal microbiota and intestinal health of tilapia (GIFT, Oreochromis niloticus) - Huang, Huajing; Lin, Xiangqin; Meng, Xiaoxue; Liu, Yu; Fan, Jiongting; Zhu, Lulu; Chen, Jiaxian; Zhang, Lu; Mi, Haifeng; Deng, Junming (Frontiers in Nutrition, 2024)
A nine-week feeding trial was conducted to evaluate the effects of replacing wheat bran (WB) with palm kernel cake (PKC) or fermented palm kernel cake (FPKC) on the growth performance, intestinal microbiota and intestinal health of genetically improved farmed tilapia (GIFT, Oreochromis niloticus) (initial weight 7.00 ± 0.01 g). Eleven isonitrogenous and isolipidic experimental diets were formulated by replacing 0, 20, 40, 60, 80, and 100% of dietary WB with PKC or FPKC. Replacement of WB with PKC concentrations up to 80% had no significant effect on the growth rate of tilapia or feed utilisation (p > 0.05). FPKC improved the growth performance of tilapia, with optimum growth achieved at 40% replacement level (p < 0.05). Complete replacement with PKC significantly decreased the activity of lipase and trypsin, and reduced the height of muscularis and the height of villus (p < 0.05). However, FPKC significantly increased amylase activity and villus height (p < 0.05). The apparent digestibility of dry matter and energy decreased linearly with increasing levels of PKC substitution, while FPKC showed the opposite trend (p < 0.05). PKC replacement of WB by 20% significantly reduced serum diamine oxidase activity and endothelin levels and increased intestinal tight junctions (p < 0.05). However, FPKC significantly decreased diamine oxidase activity and increased intestinal tight junctions (p < 0.05). PKC completely replaced WB, up-regulating the expression of pro-inflammatory factors (il-1β) (p < 0.05). When 40% of WB was replaced with FPKC, the expression of pro-inflammatory factors (il-1β and il-6) was decreased significantly (p < 0.05). Completely replacement of WB with PKC reduced the abundance of Firmicutes and Chloroflexi, while FPKC reduced the abundance of Fusobacteriota and increased the levels of Actinobacteriota. WB can be replaced with PKC up to 80% in tilapia feeds. However, the high percentage of gluten induced intestinal inflammation, impaired gut health, and reduced dietary nutrient utilisation and growth performance. Complete replacement of WB with FPKC promoted intestinal immunity. It also improved dietary nutrient utilisation and growth performance. However, the optimal growth was achieved at a 40% replacement level.